An Introductory Module and Experiments To Improve the Graphing Skills of Non-Science Majors - Violin, Christy R. (J Microbiol Biol Educ, 2018)
Graphing allows for the succinct communication of scientific data and is therefore a critical learning objective in science curricula. Unfortunately, many students, particularly non-science majors, lack the necessary skills to prepare and interpret graphs. Many students are able to interpolate data and observe general trends but demonstrate only a cursory ability to contextualize their results. In this paper, we suggest an introductory module and graphing lessons to improve the quantitative skills of non-science majors. In each of these lessons, students go through four phases of data analysis: (a) collection; (b) graphing; (c) interpolation/trend detection (reading), and (d) determining the underlying mechanism resulting in the trends they observe (interpretation). By employing these activities, we are continuing to improve the scientific literacy of students.